Pelvic floor muscle training in mother fit healthcare centres: a best practice implementation project. Issue 2 (8th June 2022) - Ghaderi, Fariba; Hajebrahimi, Sakineh; Ghaderi, Farzaneh; Pashazadeh, Fariba
ABSTRACT: Introduction and aims: Pelvic floor dysfunctions are common complications during the childbirth process. Pelvic floor muscle training (PFMT) has been used as a conservative treatment in both prenatal and postnatal women. The aim of this project was to assess the compliance with evidence-based criteria regarding PFMT among prenatal and postnatal women in mother fit healthcare centres. Methods: The current study was performed in three phases. Phase 1: stakeholder engagement and team establishment and baseline audit. Phase 2: Design and implementation of strategies to improve PFMT among prenatal and postnatal women in mother fit healthcare centres. Phase 3: Follow-up audit. Baseline and follow-up audit with six yes/no audit questions was performed using the Joanna Briggs Institute Practical Application of Clinical Evidence System. Fifteen midwives involved in prenatal and postnatal healthcare centres and 60 pregnant women participated in this study. Results: The compliance for each audit criterion found in the baseline audit was low (0–7%). However, after implementation of the project and training the trainers (midwives), the compliance increased significantly (77–100%). Conclusion: The current study demonstrated that we have some problems in the healthcare system to teach PFMT to pregnant women. We should also implement similar projects in all healthcare centres country wide. Healthcare system managers should be aware of the value of holding PFMT courses for pregnant women and it is recommended to use pelvic floor physiotherapists to train midwives.